2012
DOI: 10.6061/clinics/2012(12)07
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk and anthropometric evaluation in pediatric liver transplantation

Abstract: OBJECTIVE:To analyze the nutritional status of pediatric patients after orthotopic liver transplantation and the relationship with short-term clinical outcome.METHOD:Anthropometric evaluations of 60 children and adolescents after orthotopic liver transplantation, during the first 24 hours in a tertiary pediatric intensive care unit. Nutritional status was determined from the Z score for the following indices: weight/age, height/age or length/age, weight/height or weight/length, body mass index/age, arm circumf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
24
0
5
Order By: Relevance
“…The early nutritional intervention associated with the low percentage of severe cases in the sample may explain why the number of malnourished children in our sample was lower than that reported in other similar investigations. Our study demonstrates 28.8% of malnutrition, while others who evaluated the nutritional status in a similar way as Saron et al [19], Baran et al [20] and Zamberlan et al [21] showed percentages between 40 and 50.…”
Section: Discussionmentioning
confidence: 69%
“…The early nutritional intervention associated with the low percentage of severe cases in the sample may explain why the number of malnourished children in our sample was lower than that reported in other similar investigations. Our study demonstrates 28.8% of malnutrition, while others who evaluated the nutritional status in a similar way as Saron et al [19], Baran et al [20] and Zamberlan et al [21] showed percentages between 40 and 50.…”
Section: Discussionmentioning
confidence: 69%
“…Foram encontrados sete artigos com menos de 10 anos de publicação passíveis de comparação com o presente estudo: quatro brasileiros [15][16][17][18] e três internacionais [19][20][21] . Esses estudos utilizaram os índices E/I e/ou DCT/I para a classificação do estado nutricional e os modelos PELD e/ou MELD e/ou o escore Child-Pugh para a classificação da gravidade da doença.…”
Section: Resultsunclassified
“…Nos estudos de Baran et al 20 e de Zamberlan et al 16 , os pacientes pediátricos portadores de cirrose foram avaliados no pré e pós-transplante hepático. Segundo o resultado de Baran et al, 43,7% dos pacientes estavam desnutridos na avaliação do pré-transplante hepático 20 .…”
Section: Discussionunclassified
“…Pediatric solid organ transplant recipients, a unique chronic disease population, have long‐standing malnutrition concerns related to their pretransplant medical status . Many pediatric transplant recipients have experienced a prolonged period of debilitation before the transplant and are malnourished during their post‐transplant recovery period . Children should be introduced to solid foods when they are developmentally ready because failure to do so can result in refusal of solid foods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the chronic liver disease population is at increased risk for malnutrition, particularly as liver diseases worsens, and there is a greater metabolic demand for energy, protein, and micronutrients. Patients with chronic liver disease also deal with many feeding complications that affect nutrition status including early satiety, poor intake, increased energy expenditure, intestinal malabsorption, cholestasis, abdominal fullness, and altered taste and smell . Early satiety and anorexia occur secondary to organomegaly, portal hypertension with resulting congestive gastropathy/enteropathy, and ascites.…”
Section: Introductionmentioning
confidence: 99%